An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Effects of curcumin supplementation in high-fat diet on growth performance, antioxidant capacity and lipid metabolism of spotted sea bass (Lateolabrax maculatus) - Xiujuan Wang; Zhangfan Huang; Luming Kong; Hao Lin; Sishun Zhou; Jianrong Ma; Yanbo Zhao; Yunting Zhao; Longhui Liu; Zhongbao Li (Fish Physiology and Biochemistry, 2026)

Divergent response of vegetation structure to land-atmosphere droughts across aridity gradients in the Northern Hemisphere - Bingxin Ma; Longhui Li; Yue Zhang; Yueyue Dou; Lin Yu (Global and Planetary Change, 2026)

Optimization of Cutter Body Parameters for Milled-Tooth Roller Cutters in Shaft Sinking by Drilling Methods: A Case Study in Jurassic Strata of Western China - Xiaoyun Wang; Hua Cheng; Zhishu Yao; Jian Lin; Longhui Guo; Liangliang Zhang (Rock Mechanics and Rock Engineering, 2026)

Embryonic exposure to nanoplastics affects the metabolism and locomotor performance of a soil-dwelling, oviparous skink - Xinni He; Jiahui Xu; Shufang Zhang; Mengzhen Hu; Congcong Wang; Miao Guan; Peng Li; Lian Chen; Longhui Lin; Georgia Ward-Fear; Hong Li (Environmental Pollution, 2025)

SHAPAttention: A novel approach to enhance model performance and interpretability in agricultural spectral data analysis - Ting Wu; Longhui Zhu; Lei Li; Leian Liu; Weidong Bai; Li Lin; Ling Yang (Computers and Electronics in Agriculture, 2025)

The potential effects of inulin on lipid metabolism disorders in spotted sea bass (Lateolabrax maculatus) induced by a high-fat diet - Fuqiang Quan; Xiujuan Wang; Zhangfan Huang; Lumin Kong; Yi Lin; Hao Lin; Sishun Zhou; Jianrong Ma; Yanbo Zhao; Yunting Zhao; Longhui Liu; ZhongBao Li (Aquaculture, 2025)

The effects of dietary supplementation with Enteromorpha prolifera polysaccharide on the growth, immunity, and antioxidant capacity of spotted sea bass Lateolabrax maculatus - Zhongying Long; Longhui Liu; Huihui Qin; Sishun Zhou; Lumin Kong; Jianrong Ma; Hao Lin; Zhangfan Huang; Yi Lin; Zhongbao Li (Aquaculture International, 2025)

Transcriptome analysis of the effects of Porphyra yezoensis polysaccharide on non-specific immunity of spotted sea bass, Lateolabrax maculatus - Hao Lin; Sishun Zhou; Jianrong Ma; Lumin Kong; Zhangfan Huang; Longhui Liu; Yanbo Zhao; Yi Lin; Zhongbao Li (Aquaculture International, 2025)

Correction to: Effects of an intraoperative intravenous Bolus Dose of Dexmedetomidine on postoperative catheter-related bladder discomfort in male patients undergoing transurethral resection of bladder tumors: a randomized, double-blind, controlled trial - Tianhua Zhang; Huiting Li; Chunnan Lin; Rui An; Wenqian Lin; Hongying Tan; Longhui Cao (European Journal of Clinical Pharmacology, 2025)

Correction to: Potential effects of inulin as a dietary supplement on immunity, antioxidant, and intestinal health of spotted sea bass (Lateolabrax maculatus) fed a high‑fat diet - Fuqiang Quan; Xiujuan Wang; Luimin Kong; Yi Lin; Hao Lin; Sishun Zhou; Jianrong Ma; Yanbo Zhao; Yunting Zhao; Longhui Liu; ZhongBao Li (Aquaculture International, 2025)

Effects of curcumin supplementation in high-fat diet on intestinal health of spotted sea bass (Lateolabrax maculatus) - Xiujuan Wang; Fuqiang Quan; Zhangfan Huang; Luming Kong; Yi Lin; Hao Lin; Sishun Zhou; Jianrong Ma; Yanbo Zhao; Yunting Zhao; Longhui Liu; Zhongbao Li (Aquaculture International, 2025)

Potential effects of inulin as a dietary supplement on immunity, antioxidant, and intestinal health of spotted sea bass (Lateolabrax maculatus) fed a high-fat diet - Fuqiang Quan; Xiujuan Wang; Luimin Kong; Yi Lin; Hao Lin; Sishun Zhou; Jianrong Ma; Yanbo Zhao; Yunting Zhao; Longhui Liu; ZhongBao Li (Aquaculture International, 2025)

Effects of Porphyra yezoensis polysaccharide on antioxidant and liver health of spotted sea bass, Lateolabrax maculatus - Hao Lin; Sishun Zhou; Jianrong Ma; Lumin Kong; Zhangfan Huang; Yi Lin; Longhui Liu; Yanbo Zhao; Zhongbao Li (Aquaculture International, 2025)

Investigating climatic drivers of snow phenology by considering key-substage heterogeneity - Xinqi Ma; Kai Lin; Xueyan Sun; Lun Luo; Ning Ma; Hang Zha; Longhui Zhang; Shizhen Tang; Zhiguang Tang; Hongbo Zhang (Journal of Hydrology, 2024)

Differential mineral diagenetic evolution of lacustrine shale: Implications for CO2 storage - Liu Wang; Bo Liu; Longhui Bai; Lin Ma; Zhichao Yu; Qiuli Huo; Kevin G. Taylor (International Journal of Coal Geology, 2024)

Reduced Proteolipid Protein 2 promotes endoplasmic reticulum stress-related apoptosis and increases drug sensitivity in acute myeloid leukemia - Fahui Xie; Jia Qu; Dainan Lin; Kexin Feng; Mingzhu Tan; Haixiu Liao; Longhui Zeng; Qingquan Xiong; Jun Huang; Weiwen Chen (Molecular Biology Reports, 2024)

Lead-rivet strategy of growing perovskite nanocrystals for excellent toxicity inhibition and spinning application - Hanlong Wang; Shifeng Zhu; Jiaoyue Sheng; Feihong Gao; Lei Yang; Xili Hu; Francisco Fernández-Martínez; Longhui Lin; Chaoyu You; Dongming Xing (Journal of Hazardous Materials, 2024)

Analyzing the influence of Clostridium butyricum on liver health in spotted sea bass (Lateolabrax maculatus) via transcriptomics and metabolomics - Lumin Kong; Jianrong Ma; Hao Lin; Sishun Zhou; Zhongying Long; Huihui Qin; Yi Lin; Longhui Liu; Zhangfan Huang; Zhongbao Li (Aquaculture International, 2024)

Effects of chlorogenic acid supplementation in high-fat diet on antioxidant capacity, immunity, and intestinal health of spotted sea bass (Lateolabrax maculatus) - Jianrong Ma; Lumin Kong; Hao Lin; Sishun Zhou; Yi Lin; Huihui Qin; Zhongying Long; Longhui Liu; Zhangfan Huang; Zhongbao Li (Aquaculture International, 2024)

Nanoplastic pollution changes the intestinal microbiome but not the morphology or behavior of a freshwater turtle - Shuo Gao; Shufang Zhang; Jiahui Sun; Xinni He; Shaoshuai Xue; Wenyi Zhang; Peng Li; Longhui Lin; Yanfu Qu; Georgia Ward-Fear; Lian Chen; Hong Li (Science of The Total Environment, 2024)

Evaluation of quercetin in alleviating the negative effects of high soybean meal diet on spotted sea bass Lateolabrax maculatus - Longhui Liu; Yanbo Zhao; Zhangfan Huang; Zhongying Long; Huihui Qin; Hao Lin; Sishun Zhou; Lumin Kong; Jianrong Ma; Yi Lin; Zhongbao Li (Fish & Shellfish Immunology, 2024)

Advances in membrane-tethered NAC transcription factors in plants - Lin Shu; Longhui Li; Yuan-Qing Jiang; Jingli Yan (Plant Science, 2024)

Effects of an intraoperative intravenous Bolus Dose of Dexmedetomidine on postoperative catheter-related bladder discomfort in male patients undergoing transurethral resection of bladder tumors: a randomized, double-blind, controlled trial - Tianhua Zhang; Huiting Li; Chunnan Lin; Rui An; Wenqian Lin; Hongying Tan; Longhui Cao (European Journal of Clinical Pharmacology, 2024)

Growth performance, digestive capacity and intestinal health of juvenile spotted seabass (Lateolabrax maculatus) fed dietary laminarin supplement - Huihui Qin; Zhongying Long; Jianrong Ma; Lumin Kong; Hao Lin; Sishun Zhou; Yi Lin; Zhangfan Huang; Longhui Liu; Zhongbao Li (Frontiers in Marine Science, 2023)
Laminarin has antioxidant and immunomodulatory properties and favorably impacts gut microbial composition, providing a potential solution for the treatment of intestinal diseases in fish. The aim of this study was to investigate the effects of laminarin on the growth and intestinal health of juvenile spotted seabass, Lateolabrax maculatus . A total of 450 juveniles (initial body weight: 7.14 ± 0.10 g) were randomly divided into 6 groups with 3 replicates per group and 25 fish per replicate. Six diets were prepared with laminarin supplementation at doses of 0% (Control), 0.4% (P0.4), 0.8% (P0.8), 1.2% (P1.2), 1.6% (P1.6), and 2% (P2). Each group was fed the corresponding diet for 8 weeks. The results indicated that dietary laminarin supplementation of 0.4-1.6% enhanced the specific growth rate (SGR), weight gain rate (WGR), and feed conversion ratio (FCR) of juvenile spotted seabass, and the difference was significant in the P0.8 group ( P <0.05). Significantly higher intestinal amylase activity was measured in P0.8 compared with the control group. Trypsin activity was significantly increased in P0.4 and P0.8 groups in contrast to the control ( P <0.05). Lipase activity was significantly increased in P0.4, P0.8, P1.6, and P2 groups in contrast to the control ( P <0.05). Total antioxidant capacity was significantly increased in the P0.8, P1.2, and P1.6 groups compared to the control group ( P <0.05). The P0.8 group exhibited significant increases in reduced glutathione, alkaline phosphatase, and lysozyme levels ( P <0.05), whereas the concentrations of diamine oxidase and D-lactate were significantly decreased ( P <0.05). Furthermore, intestinal villus height, villus width, and crypt depth were significantly increased in P0.8 and P2 groups ( P <0.05), and muscular thickness was significantly increased in the P1.2 group ( P <0.05). Intestinal microbial analysis revealed that the alpha diversity of the laminarin supplemented groups was significantly higher than that of the control group. Moreover, the abundance of intestinal beneficial bacteria Lactobacillus and Klebsiella in P0.4 and P0.8 groups was significantly increased ( P <0.05), indicating that laminarin altered the composition of intestinal flora and the abundance of dominant bacteria, with a low dose being more conducive to the formation of beneficial bacteria. In conclusion, dietary laminarin supplementation can improve the growth performance and intestinal function of juvenile spotted seabass. Based on the regression analyses of weight gain rate and specific growth rate, the optimal supplemental level of laminarin was estimated to be 0.97% and 0.98%, respectively.

The Effects of Porphyra yezoensis Polysaccharides on Intestinal Health of Spotted Sea Bass, Lateolabrax maculatus - Hao Lin; Sishun Zhou; Zhangfan Huang; Jianrong Ma; Lumin Kong; Yi Lin; Zhongying Long; Huihui Qin; Longhui Liu; Yanbo Zhao; Zhongbao Li (Fishes, 2023)
Porphyra yezoensis polysaccharides (PPs) have biological activities such as promoting digestion, functioning as antioxidants, and improving intestinal health. The aim of this study was to investigate the effects of PPs on the intestinal health of spotted sea bass (Lateolabrax maculatus). A total of 360 spotted sea bass (10.53 ± 0.02 g) were randomly divided into six groups. Fish in each group were fed with varying PP concentrations (0, 3, 6, 9, 12, 15 g/kg) for 52 days. The results showed that 12 g/kg PPs significantly increased the body weight gain, specific growth rate, and condition factor, while there was no significant change in the feed conversion ratio. A supplementation dosage of 9 g/kg PPs significantly increased intestinal amylase activity, and 12 g/kg PPs supplementation significantly increased intestinal trypsin activity. In addition, compared with the control group, there was no difference in lipase in the experimental groups. When fed 9 g/kg, the intestinal glutathione content was significantly increased, and the malondialdehyde content was significantly decreased; the effect of PPs on the catalase activity was not significant. PPs improved intestinal morphology, specifically by improving the intestinal villus morphology and increasing the intestinal lining surface area. Compared with the control group, PPs increased the abundance of Firmicutes and Bacteroides. At the genus level, Cyanobacteria, Muribaculaceae, and Lachnospiraceae were the main flora in the intestinal tract of spotted sea bass. In addition, PPs increased ACE and Chao1 indices of the intestinal microorganisms, while the Simpson index and Shannon index did not change significantly, indicating that intestinal microbial composition and abundance had increased to a certain extent. The results indicated that different levels of PPs in feed can improve the intestinal physiological and biochemical indexes, intestinal morphology, and microbial composition, and thus improve the intestinal health of spotted sea bass.

Effects of mulberry leaf extract on the intestinal health of spotted sea bass (Lateolabrax maculatus) - Sishun Zhou; Zhangfan Huang; Hao Lin; Lumin Kong; Jianrong Ma; Zhongying Long; Huihui Qin; Longhui Liu; Yi Lin; Zhongbao Li (Frontiers in Marine Science, 2023)
Mulberry leaf extract (ELM) has the functions of promoting growth, antioxidant, improving intestinal microbial composition, thus providing a potential solution the occurrence of fish intestinal diseases. Therefore, this experiment was conducted to explore the effects of ELM on intestinal health of spotted sea bass Lateolabrax maculatus . A total of 360 spotted sea bass (9.00 ± 0.02 g) were selected and randomly divided into 6 groups. Fish in each group were given feed with varying ELM concentration (0, 3, 6, 9, 12, 15 g/kg) for 52 days, respectively. Results show, dietary intake of 9 g/kg ELM increased the weight gain, specific growth ratio and feed intake of the spotted sea bass ( P <0.05). Meanwhile, dietary intake of 9 g/kg ELM increased the activity of enteric trypsin, amylase and lipase ( P <0.05). The enteric catalase activity was improved in fish fed with 3 g/kg ELM ( P <0.05), while a limited effect of ELM on the activity of enteric superoxide dismutase, glutathione, and content of malonaldehyde was observed ( P >0.05). ELM improved the morphology of fish intestine, as manifested in significant improvement in the length of intestinal villi, thereby increasing the surface area of the intestinal tract ( P <0.05). Compared with the control group, dietary intake of ELM significantly increased the intestinal microbial ACE, Chao1, and Shannon indexes of fish ( P <0.05), indicated that the intestinal microbial composition and the abundance of the dominant flora of fish were improved. The above results suggested that the dietary supplementation of about 9 g/kg ELM can improve the growth performance, enteric antioxidant capacity, and intestinal morphology and microbial composition, therefore improving the intestinal health of spotted sea bass. The research results provide a theoretical basis for the application of ELM in improving the enteric health of spotted sea bass, and providing a potential solution the occurrence of fish intestinal diseases.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Genetic controls of Tas1r3-independent sucrose consumption in mice - Cailu Lin; Michael G. Tordoff; Xia Li; Natalia P. Bosak; Masashi Inoue; Yutaka Ishiwatari; Longhui Chen; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)